A Study on the Performance of the Competition Commission and Competition Law in Bangladesh: Qualitative Content Analysis of the ‘Other Opinion’ (Dhaka University Law Journal, 2024)
The researchers conducted a series of Key Informant Interviews among expert respondents having good experience in competition law and the Competition Commission of Bangladesh. After conducting a qualitative content analysis, the data of the first-of-its-kind study were later presented for research publications. While the questionnaire comprised of fixed questions was subject to publication in different journals, the data analysis results of ‘other opinion’ were chosen for this article. The respondents brought forward various issues our fixed questions did not address. Findings and recommendations were heavily drawn from the outcome of the qualitative data analysis of the ‘other opinion’. The authors also provided a legal background to co-relate the issues of ‘competition’ with the legitimate or illicit practice of ‘anticompetitive market behavior’.Dhaka University Law Journal, 2023, 34 (2), 25-41